2013
DOI: 10.1128/mcb.00879-13
|View full text |Cite
|
Sign up to set email alerts
|

PLEKHG2 Promotes Heterotrimeric G Protein βγ-Stimulated Lymphocyte Migration via Rac and Cdc42 Activation and Actin Polymerization

Abstract: PLEKHG2 is a Dbl family Rho guanine nucleotide exchange factor (RhoGEF) whose gene was originally identified as being upregulated in a leukemia mouse model and was later shown to be activated by heterotrimeric G protein ␤␥ (G␤␥) subunits. However, its function and activation mechanisms remain elusive. Here we show that, compared to its expression in primary human T cells, its expression is upregulated in several leukemia cell lines, including Jurkat T cells. Downregulation of PLEKHG2 in Jurkat T cells by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Swap70 44 ) or can directly bind Gβγ (Dbl 45 ), the synergistic activation by PIP 3 and Gβγ is unique to the P-Rex family. Several other Rac-GEFs can be activated by Gβγ in vivo, including PLEKHG2 46 and DOCK180/Elmo1, 47 but as yet without evidence for direct activation in vitro. The most promising example for direct Gβγ-dependent activation of GEFs other than P-Rex is for DOCK/Elmo complexes in Dictyostelium, where direct Gβγ binding to ElmoE was suggested by FRET, 48 although direct Gβγ-dependent activation of DOCK/Elmo remains to be confirmed with recombinant proteins.…”
Section: Regulation Of Activitymentioning
confidence: 99%
“…Swap70 44 ) or can directly bind Gβγ (Dbl 45 ), the synergistic activation by PIP 3 and Gβγ is unique to the P-Rex family. Several other Rac-GEFs can be activated by Gβγ in vivo, including PLEKHG2 46 and DOCK180/Elmo1, 47 but as yet without evidence for direct activation in vitro. The most promising example for direct Gβγ-dependent activation of GEFs other than P-Rex is for DOCK/Elmo complexes in Dictyostelium, where direct Gβγ binding to ElmoE was suggested by FRET, 48 although direct Gβγ-dependent activation of DOCK/Elmo remains to be confirmed with recombinant proteins.…”
Section: Regulation Of Activitymentioning
confidence: 99%
“…Cdc42 is a vital factor in cell phagocytosis, which is an actin-dependent process essential to the host defense mechanism (9). Cdc42 plays a role in actin polymerization (10)(11)(12) and can regulate gene transcription in various signaling pathways, such as the NF-B, NOD1, c-Jun N-terminal kinase (JNK), and mitogen-activated protein kinase (MAPK) pathways (7,13). Alternatively, several RNA virus species, including human immunodeficiency virus type 1 (HIV-1), respiratory syncytial virus (RSV), and Ebola virus (EBOV), have developed a diverse repertoire of mechanisms to hijack cellular actin-regulating signaling pathways as part of their cell entry processes.…”
mentioning
confidence: 99%
“…activity of PLEKHG2. Recently, we and other researchers suggested that the C terminus of PLEKHG2 might interact with the N terminus of PLEKHG2, and this interaction could impose a constraint on the normal DH domain function by masking the access of the Rho GTPase (9,15). It has been hypothesized that, when PLEKHG2 is activated, the interaction between the C and N termini is canceled, and the DH domain functions as a guanine nucleotide exchange factor for the Rho protein.…”
Section: The Interaction Of Plekhg2/flj00018 With Fhl1mentioning
confidence: 99%